Effectiveness and Safety of Baclofen in the Treatment of Alcohol Dependent Patients - Leggio, Lorenzo; Garbutt, James C.; Addolorato, Giovanni (CNS & Neurological Disorders - Drug Targets, 2010)
Both preclinical and clinical research studies have shown the GABAB receptor agonist baclofen represents a promising treatment for alcohol dependence. Preliminary clinical studies indicate that baclofen is able to suppress withdrawal symptoms in alcoholdependent patients affected by the alcohol withdrawal syndrome. Moreover, baclofen has shown efficacy and safety in promoting alcohol abstinence in alcohol dependent patients in two placebo-controlled trials including one in alcohol-dependent patients with liver cirrhosis. These trials also demonstrated that baclofen was associated with reductions in withdrawal-related anxiety and alcohol craving. However, more work is needed to clearly demonstrate the efficacy of baclofen and to ascertain whether efficacy is limited to certain subtypes of alcoholic patients. For example, a recent US trial failed to demonstrate a robust effect of baclofen in treating alcohol-dependent patients though the relative moderate severity of alcohol-dependence in that trial has been suggested as one factor that may have contributed to the finding. In the present review, the authors will summarize the published clinical studies on the role of baclofen in alcohol dependence and will also present some unpublished secondary analyses. Finally, the authors will discuss possible future directions to further investigate the role of baclofen in alcohol dependence (e.g., baclofen's biobehavioral mechanisms, different baclofen doses, differences in severity and in alcoholic subtypes, different formulations of baclofen, possible combination of baclofen with other medications).
Keywords: alcoholic cirrhosis